2020
DOI: 10.1002/ecy.3176
|View full text |Cite
|
Sign up to set email alerts
|

Lianas maintain insectivorous bird abundance and diversity in a neotropical forest

Abstract: The spatial habitat heterogeneity hypothesis posits that habitat complexity increases the abundance and diversity of species. In tropical forests, lianas add substantial habitat heterogeneity and complexity throughout the vertical forest profile, which may maintain animal abundance and diversity. The effects of lianas on tropical animal communities, however, remain poorly understood. We propose that lianas have a positive effect on animals by enhancing habitat complexity. Lianas may have a particularly strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…For example, Michel et al (2015a) argue that the most plausible explanation for the decline of insectivorous birds from some Central American forests is the local increase of collared peccaries (Pecari tajacu): This study focused on three unrelated insectivorous bird species in multiple Central American sites, and showed that (a) these species foraged preferentially in vine and liana tangles, (b) such viney substrates are more abundant where peccaries are least abundant (including experimental peccaryexclosure plots), and (c) abundant peccaries are associated with reduced abundance of these particular bird species. This lianasubstrate hypothesis is reinforced by the variety of insects that frequent vines and lianas (Schnitzer et al, 2020).…”
Section: Insect Declinesmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Michel et al (2015a) argue that the most plausible explanation for the decline of insectivorous birds from some Central American forests is the local increase of collared peccaries (Pecari tajacu): This study focused on three unrelated insectivorous bird species in multiple Central American sites, and showed that (a) these species foraged preferentially in vine and liana tangles, (b) such viney substrates are more abundant where peccaries are least abundant (including experimental peccaryexclosure plots), and (c) abundant peccaries are associated with reduced abundance of these particular bird species. This lianasubstrate hypothesis is reinforced by the variety of insects that frequent vines and lianas (Schnitzer et al, 2020).…”
Section: Insect Declinesmentioning
confidence: 98%
“…Lost insect substrates and microhabitats may be as important causes of bird declines as insect declines per se (Stratford and Stouffer, 2015;, although the two may be linked as in the case of tropical lianas (Schnitzer et al, 2020). Neotropical insectivorous birds are often substrate specialists, inferred from stereotyped feeding habits linked to morphology and behavior (Sherry, 1990, Supplementary Table 2), and the loss of which could jeopardize a variety of these birds' survival.…”
Section: Insect Declinesmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of animals, including invertebrates, arboreal mammals, and many bird species use lianas as a food source, eating liana leaves, pollen, flowers, and fruits (Odell et al 2019). Many invertebrate herbivores specialize on liana species (Ødegaard 2000), and insectivorous bird species may feed on these specialized herbivores (Schnitzer et al 2020). Climbing animals such as monkeys, sloths, rodents, and ants depend on the structure and connectivity that lianas provide in the forest canopy (Chiarello et al 2004, Adams et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, while preventing degraded forests from conversion could protect biodiversity, this study only considers the impact of climber removal on tree and AGB growth, ignoring the various functions of climbing plants in tropical forests. Their removal could have negative consequences for biodiversity, for example reducing the species richness of climbing plants, removing food and locomotion resources, and influencing the microclimate (Addo‐Fordjour et al, 2020 ; Arroyo‐Rodriguez et al, 2015 ; Campbell et al, 2015 ; Cosset & Edwards, 2017 ; Magnago et al, 2017 ; Putz et al, 2001 ; Schnitzer et al, 2020 ), though see Cerullo et al ( 2019 ). Our study finds that applying removal just to focal trees and not repeating treatment yield growth benefits while giving climbers greater chance to recover, but this will not be enough to prevent biodiversity losses from climber removal.…”
Section: Discussionmentioning
confidence: 99%